Formation and Characterization of Ni Nanofiber Catalysts on Nickel Metallic Foam by Electrospinning Process - Yeom, Hee Chul; Moon, Dong Ju; Lee, Kwan Young; Kim, Sang Woo (AMER SCIENTIFIC PUBLISHERS, 2015)
We report the fabrication of nickel nanofiber catalysts supported on nickel metallic foam using a modified electrospinning with a grounded rotor and sequential reduction process. The robust deposition of aligned Ni nanofibers with a uniform morphology on the highly porous surfaces of the metallic foam could be achieved by controlling electrospinning parameters such as applied voltage, tip-collector-distance (TCD), concentration of polymer, and humidity. The diameters of the obtained nanofibers decreased with increasing voltage and TCDs. The uniform and thinnest Ni nanofibers on the Ni foam were obtained at a humidity of less than 30%, 15 kV applied voltage, and 17 cm TCD when using a precursor composed of nickel nitrate salt and poly(vinyl) pyrrolidone. The Ni foam catalyst support exhibited the superior thermal conducting property than other supports of MgO MgAl2O4, Al2O3, and SiC, enabling to a higher heat transfer during catalytic reaction. As a result, the Ni nanofiber catalyst with a high surface area and superior heat transfer performance, which is supported on the metallic foam, were successfully fabricated via a modified electrospinning for potential application of XTL process converting anything to liquids, such as for Gas-to-Liquid (GTL), Coal-to-Liquid (CTL), and Biomass-to-Liquid (BTL).
Keywords: STABILITY